Effect Of Curcumin And Honey To Pharmacokinetics Of Paracetamol In Male Wistar Rats - Dimas Adhi Pradana; Farida Hayati; Agung Giri Samudra; Amalinda Setya Kartika (EKSAKTA: Journal of Sciences and Data Analysis, 2011)
Honey and curcumin is widely consumed by children as food supplements. Honey is useful as an antioxidant and antibacterial, while curcumin  is useful as an antioxidant, antiinflammatory,  antibacterial,  antiviral. Both  health  supplements  are  not  infrequently used in conjunction with drugs, especially paracetamol. This study aims to determine the effect of curcumin and honey on the pharmacokinetic parameters of paracetamol in male rats.  In  this  study,  test  animals  were  divided  into  3  groups:  control,  treatment  I  and treatment  II.  In  the  control  group  mice  were  given  paracetamol  150mg  /  KgBW, treatment  group  I  rats  were  given  curcumin  18  mg  /  KgBW,  1  hour  and  then  given paracetamol 150mg  / KgBW whereas  the  treatment group  II  rats given a dose of honey 7.65 mL / KgBW along with giving paracetamol 150mg KgBB . The results showed that administration of curcumin on the pharmacokinetics of paracetamol in mice can decrease the  primary  parameters  of  the  elimination  phase  of  CLT  for  68.25%,  increasing  the secondary parameter t 1 / 2 at 193.72%, thus increasing the derivative parameters AUC0-inf for 88.36%, and MRT of 155.17% (p